9 - The Ten Thinkers who want to Complete the Emancipation of the African Continent: Portraits of the Most Prolific Intellectuals in the Revival of “Decolonised” African Plural Thinking - Kodjo-Grandvaux, Séverine (CODESRIA Bulletin, 2021)
At the initiative of Felwine Sarr and Achille Mbembe, the first edition of series of ‘thought Workshops’ will be held in Dakar on Friday 28 October 2016. This is expected to be a historical event with the Senegalese writer and Cameroonian historian inviting many African intellectuals to participate in reviving African plural thinking that is free, inter-alia, from post-colonialism, a "mental decolonisation ven-ture". Portraits: